In vitro activity of piperazine derivates against multidrug-resistance bacteria - Caro Ruiz, Gabriel; Cebrero Cangueiro, Tania; Labrador Herrera, Gema; Pachón, Jerónimo; Pachón-Ibáñez, María Eugenia (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2016)
Motivation: The increasing prevalence of multidrug-resistance represent a serious challenge for clinical management and public health. Multidrug-resistant (MDR) bacteria is a common cause of infections, especially in inmunocompromised patient. Nowadays, colistin has re-emerged as one of the last therapeutic option against these kinds of infections, but colistin resistant strains have been reported, leaving no alternative of treatment. The aim of this work is to study in vitro the activity of piperazine derivates against MDR and colistin resistant bacteria. Methods: Clinical and standard strains: MDR: Acinetobacter baumannii (Ab; n=1), Klebsiella pneumoniae carbapenemases producing (n=4), Pseudomonas aeruginosa (Pa; n=2), Escherichia coli ATCC 25922 (n=1), colistin resistant A. baumannii (n=13). Piperazine derivatives: four different families were tested: 1, 2, 3, and 4. The derivivates were synthesized in the Pharmacy Faculty of Seville. A) Inhibition screening: all strains at a concentration of 5x105 CFU/mL were tested at 50 µM of each derivative. B) Minimal Inhibitory Concentration (MIC): were calculated for the derivates that inhibit the bacterial growth. C) Time-kill curves: were performed for six derivates against two colistin resistant A. baumannii clinical strains. Results: A) Inhibition was observed only in colistin resistant A. baumannii clinical strains. B) Family 1, inhibited the growth of 46 % (6/13) of the strains. Family 2, inhibited the growth of 30% (4/13) of the strains. Family 3, inhibited the growth of 30% (4/13) of the strains. Family 4, inhibited the growth of 38% (5/13) of the strains. C) Family 1: MIC range was 50-3.12 µM. Family 2: MIC range was 50-6.25 µM. Family 3: MIC range was 50-1.56 µM. Family 4: MIC range was 50-3.12 µM. D) One piperazine derivates presented bactericidal activity at 24 hours against one of the tested strains. Conclusions: Piperazine derivatives showed in vitro activity against colistin resistant A. baumannii clinical strains. Further studies, in vitro and in vivo need to be performed in order to confirm the activity of the piperazine derivates against infections due to these kinds of infections.